Comparison of Reconstructive Outcomes in Breast Cancer Patients With Preexisting Subpectoral Implants: Implant-Sparing Mastectomy With Delayed Implant Exchange Versus Immediate Tissue Expander Reconstruction. (June 2016) - Parabkaharan, Sangeetha; Melody, Megan; Trotta, Rose; Lleshi, Amina; Sun, Weihong; Smith, Paul D.; Khakpour, Nazanin; Dayicioglu, Deniz
Abstract : Background: Women who have undergone prior augmentation mammoplasty represent a unique subset of breast cancer patients with several options available for breast reconstruction. We performed a single institution review of surgical outcomes of breast reconstruction performed in patients with breast cancer with prior history of subpectoral breast augmentation. Methods: Institutional review board–approved retrospective review was conducted among patients with previously mentioned criteria treated at our institution between 2000 and 2014. Reconstructions were grouped into 2 categories as follows: (1) removal of preexisting subpectoral implant during mastectomy with immediate tissue expander placement and (2) implant-sparing mastectomy followed by delayed exchange to a larger implant. We reviewed demographics, tumor features, and reconstruction outcomes of these groups. Results: Fifty-three patients had preexisting subpectoral implants. Of the 63 breast reconstructions performed, 18 (28.6%) had immediate tissue expander placed and 45 (71.4%) had implant-sparing mastectomy followed by delayed implant exchange. The groups were comparable based on age, body mass index, cancer type, tumor grade, TNM stage at presentation, and hormonal receptor status. No significant difference was noted between tumor margins or subsequent recurrence, mastectomy specimen weight, removed implant volume, volume of implant placed during reconstruction, or time from mastectomy to final implant placement. Rates of complications were significantly higher in the tissue expander group compared to the implant-sparing mastectomy group 7 (38.9%) versus 4 (8.9%) ( P = 0.005). Conclusions: Implant-sparing mastectomy with delayed implant exchange in patients with preexisting subpectoral implants is safe and has fewer complications compared to tissue expander placement. There was no difference noted in the final volume of implant placed, time interval for final implant placement, or tumor margins.